Penerapan Media Konversi Pecahan untuk Meningkatkan Hasil Pembelajaran Matematika di Sekolah Dasar - Roni Rahmawanto (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this research is to improve Mathematics learning in grade V students using Fraction Conversion media. Based on preliminary observations, the teacher discovers the difficulties experienced by V grade in 2018/2019 during Mathematics learning. The results of the final semester 1 assessment obtained the average value of students in basic competency 1, namely 55, and basic competency 2, namely 47. Classroom action research was implemented to improve the process and results of learning Mathematics through the use of Fraction Conversion media. Learning material is focused on equations, addition, subtraction, multiplication, and fraction distribution. Learning outcomes data were collected using tests. Whereas, student activity data and mathematics learning skills through observation when learning takes place. Data analysis using quantitative and qualitative descriptive. The results of data analysis showed that the completeness of student mathematics learning increased from 71% to 87%. In addition, the activities and skills of students also increased due to the use of Fraction Conversion media. The conclusion is that the use of Fraction Conversion Media can improve the cognitive and psychomotor learning outcomes and processes of fifth-grade students at Ngentak Elementary School.